2012
DOI: 10.2298/tam1204365r
|View full text |Cite
|
Sign up to set email alerts
|

Homotopy simulation of axisymmetric laminar mixed convection nanofluid boundary layer flow over a vertical cylinder

Abstract: In this paper, the semi-analytical/numerical technique known as the homotopy analysis method (HAM) is employed to derive solutions for the laminar axisymmetric mixed convection boundary-layer nanofluid flow past a vertical cylinder. The similarity solutions are employed to transform the parabolic partial differential conservation equations into system of nonlinear, coupled ordinary differential equations, subject to appropriate boundary conditions. A comparison has been done to verify the obtained result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…The latter have deployed an extensive range of sophisticated algorithms. Rashidi et al (2012) used the homotopy analysis method (HAM) and Mathematica symbolic software to analyze coating flows of a vertical cylinder with nanofluids. Rashidi et al (2013) studied the Von Karman swirl flow of a nanofluid with entropy generation using differential transform methods.…”
mentioning
confidence: 99%
“…The latter have deployed an extensive range of sophisticated algorithms. Rashidi et al (2012) used the homotopy analysis method (HAM) and Mathematica symbolic software to analyze coating flows of a vertical cylinder with nanofluids. Rashidi et al (2013) studied the Von Karman swirl flow of a nanofluid with entropy generation using differential transform methods.…”
mentioning
confidence: 99%
“…Total entropy generation of nanofluids past a square cylinder in vertically upward flow decreases with increasing nanoparticle volume fractions and for mixed convection flows with nanofluids, thermal irreversibility is higher than frictional irreversibility [16]. The homotopy analysis method has excellent potential for simulating nanofluid dynamics problems for the laminar axisymmetric mixed convection boundary-layer nanofluid flow past a vertical cylinder [17]. In a steady, 3D stagnation point flow of a nanofluid past a vertical circular cylinder that has a sinusoidal radius variation, [18] and [19] it was found that the skin friction coefficient and the heat transfer rate at the surface are higher for copperwater nanofluid than alumina-water and titania-water nanofluids.…”
Section: Introductionmentioning
confidence: 99%
“…The model proposed by Buongiorno (2006) studies the Brownian motion and the thermophoresis on the heat transfer characteristics. Recently, the analytical solutions for the laminar axisymmetric mixed convection boundary layer nanofluid flow past a vertical cylinder is obtained by Rashidi et al (2012a). Stagnation point flow of nanofluid near a permeable stretched surface with thermal convective condition is provided by Alseadi et al (2012).…”
Section: Introductionmentioning
confidence: 99%